2022
DOI: 10.1371/journal.pone.0276070
|View full text |Cite
|
Sign up to set email alerts
|

Suicide capability within the ideation-to-action framework: A systematic scoping review

Abstract: Suicide capability is theorised to facilitate the movement from suicidal ideation to suicide attempt. Three types of contributors are posited to comprise suicide capability: acquired, dispositional, and practical. Despite suicide capability being critical in the movement from ideation-to-attempt, there has been no systematic synthesis of empirical evidence relating to suicide capability that would enable further development and refinement of the concept. This study sought to address this synthesis gap. A scopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 212 publications
2
9
0
1
Order By: Relevance
“…Different facets of capability may be influenced by separate intrapersonal and/or contextual processes and could be differentially responsive to interventions. Our results are in line with recent refinements of ideation-to-action theories (e.g., Klonsky et al, 2021) and reviews (e.g., Bayliss et al, 2022) that note the considerable heterogeneity in suicide capability. Accordingly, examining capability as a unitary construct occludes within-facet differences in short-term change that may be particularly relevant to understanding periods of heightened suicide risk.…”
Section: Relations Among Facets Of Capabilitysupporting
confidence: 92%
“…Different facets of capability may be influenced by separate intrapersonal and/or contextual processes and could be differentially responsive to interventions. Our results are in line with recent refinements of ideation-to-action theories (e.g., Klonsky et al, 2021) and reviews (e.g., Bayliss et al, 2022) that note the considerable heterogeneity in suicide capability. Accordingly, examining capability as a unitary construct occludes within-facet differences in short-term change that may be particularly relevant to understanding periods of heightened suicide risk.…”
Section: Relations Among Facets Of Capabilitysupporting
confidence: 92%
“…Taken together, the suicidal mental imagery findings from this study provide tentative empirical support for a cognitive facet of suicide capability as suggested by Bayliss et al (2022). Furthermore, these findings are in accordance with recent research focusing on adolescents that found suicidal mental imagery differentiated ideators and attempters (De Rozario et al, 2021).…”
Section: Suicidal Mental Imagerysupporting
confidence: 90%
“…In addition to findings that imagery can differentiate suicide attempters from suicide ideators (De Rozario et al, 2021;Wetherall et al, 2018), imagery can be dynamic (Zaleskiewicz et al, 2023) and episodic (Lawrence et al, 2023) and therefore appropriate for EMA studies. Furthermore, suicidal cognitions, such as mental imagery, are not currently considered as part of suicide capability despite a recent review reporting cognitive differences between suicide attempters and ideators (Bayliss et al, 2022). Given the above, imagery warrants further investigation within suicide-focused EMA studies.…”
Section: Introductionmentioning
confidence: 99%
“…As supported by other studies, distress (Items 3, 6, 7, 8, 12, 14, 20) [64][65][66][67][68][69], depression and substance use disorder (SUD) ( Items 3,4,5,8,9,12,15,18,19,20,21) [1,67,[70][71][72] are strong predictors of NSSI. Despite existing in questionnaires previously, Emotional Reactivity (ER) has been recently proven to be a contributing factor for NSSI identification (Items 12, 16, 21, 22) [73].…”
Section: Plos Onementioning
confidence: 59%
“…NSSI and suicidal behaviors can be differentiated by (but not limited to) nine major factors: intent, lethality, chronicity, methods and functions, cognitions, reactions, aftermath, demographics, and prevalence [5]. While NSSI is primarily intended to eliminate 1) negative emotion, 2) body alienation (dissatisfaction), and 3) dissociation, suicide tends to be a way out of all of them at once when the injurers are not satisfied with the deceptive temporary pain caused by injuries, nor are they cured via therapies [1,5,[16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%